IHI ID 09 A quality improvement (QI) initiative to decrease diagnostic errors. (December 2018) - McClead, Richard; Kasick, Rena; Perry, Michael; Melvin, Jennifer; Kersey, Kelly; Kamboj, Manmohan; Hill, Ivor; Noritz, Garey; Bode, Ryan; Stevens, Jack; Ballenger, Taylor; Hoffman, Jeff
Abstract : Background: Diagnostic errors (DE) in healthcare are a widespread, but underappreciated, problem. Investigators report that everyone will experience at least one DE in their lifetime. Objectives: After the occurrence of six serious adverse events related to DE in the first six months of 2015, we chartered a QI team in 2016 to decrease DE. Methods: The team used QI methodology, established a specific aim and key driver diagram (figure 1 ), and developed the diagnostic error index (DEI 1.0) to measure the impact of interventions to decrease DE. The DEI 1.0 consists of 5 sources of DE: class I autopsy findings, RCA with DE as a failure mode, medical record triggers, Morbidity & Mortality reports, and other adverse event reports of DE. We aimed to reduce the DEI from 7/month to 3/month by December 31, 2018. We evaluated several interventions to decrease DE including the diagnostic time out, open notes, differential diagnosis (DDx) software, EMR advisory board, pan-ophthalmoscopy, admission DDx audits, and participation in a pilot SIDM-IHI DE collaborative. Results: In January 2018, we reduced the DEI to 3.25/month and have sustained this rate for 8 months (figure 2 ). Conclusions: The most impactful intervention appears to be the diagnostic time out and emphasis on DDx. During the time out, the patient care team addresses 2 questions during rounds: What 2–3 other conditions could this be? What 1–2 diagnoses can we not afford to miss? The next steps include the development of the DEI 2.0 and an expanded trial of DDx software.